In the likely event : [large type] a novel - Yarros, Rebecca (Thorndike Press large print top shelf., 2024)
"When Izzy Astor gets on a plane to go home, she isn't expecting much. It's the usual holiday travel experience: busy, crowded, stressful. Then she spots her seatmate, who is anything but ordinary. Nate Phelan sports dark hair, blue eyes, and a deliciously rugged charm that Izzy can't resist. Their connection is undeniable. Izzy never believed in destiny before, but she does now. Just ninety seconds after takeoff, their plane goes down in the Missouri River. Their lives change. They change. Nate goes on to a career in the military while Izzy finds her way into politics. Despite a few chance encounters over the years, the timing never feels right. Then comes a high-stakes reunion in Afghanistan, where Nate is tasked with protecting Izzy's life. He'll do anything to keep her safe. And everything to win her heart"--